Marginalisation process in agriculture: indicators, outlook and policy implications - Rao, V.M.; Hanumappa, H.G. (1999)
The strategy towards the poor adopted so far has emphasised the building up of a delivery system capable of reaching the poor and providing them food, employment, assets and the like. But it has done little, despite an abundance of promises, to confront the structures and processes responsible for the poverty of the masses. No progress in human development is possible without a determined attack on these structures and processes. This paper describes the marginalisation process operating in agriculture and suggests that the process is likely to get intensified in the coming years. It is also argued that all the major determinants - the policy environment, the markets and modernised agriculture - tend to bypass the poor rather than work towards their development. The paper concludes with a brief description of a recent successful case of self-reliant development of a village community and its implications for interventions by NGOs and activists. - Reproduced
Keywords: Agriculture